Upper limb II, Hand & wrist - Hillen, Berend; Groen, Gerbrand J. (Amsterdam : Elservier Science, 1997)
(Producer) Presents over 9,000 images of normal anatomy and correlative images from CT, MRI, and histology. Enables medical professionals to explore interactively the major structures of the hand and wrist region. All structures are displayed as continuous cross-sectional photographs in coronal, sagittal, and axial directions. These images can be displayed as stills or video animation and can be viewed with or without the names of the structures in nomina anatomica.
CD is available at Koleksi Media, Perpustakaan HUKM
Also contains version issued on Cd-I disc
System requirements: IBM-compatible PC with a 33 MHz 486 CPU or better (will run on a minimum of 386 CPU, but video playback will be at a lower speed); 4 Mb internal memory, 5 Mb available on hard disk for installation; MS-Windows 3.1; a better CD-ROM player with adequate access time (less than 400 milliseconds); mouse or other pointing device compatible with MS-Windows; accelerated 256 color VGA adapter compatible with MS-Windows (resolution 640 x 480) (will run on a non-accelerated VGA adapter, but video playback will be at a lower speed).
System requirements: CD-i player upgraded with digital video (DV) cartridge
Keywords: Hand -- anatomy & histology -- CD-ROM; Wrist -- anatomy & histology -- CD-ROM